Analysis of tracheal, bronchial, and lung cancer attributable to respiratory system-related risk factors in 204 countries and territories from 1990 to 2019 - Shiwen Yu; Liangwei Yang; Weiwen Xu; Tian Zhao; Liyuan Han; Guofang Zhao; Ting Cai (Archives of Medical Science)
Introduction We analyzed trends in the tracheal, bronchial, and lung (TBL) cancer disease burdens attributable to respiratory system-related risk factors in 204 countries and territories from 1990 to 2019.